Host variation in type I interferon signaling genes (MX1), C–C chemokine receptor type 5 gene, and major histocompatibility complex class I alleles in treated HIV+ noncontrollers predict viral reservoir size. (1st March 2023) - Siegel, David A.; Thanh, Cassandra; Wan, Eunice; Hoh, Rebecca; Hobbs, Kristen; Pan, Tony; Gibson, Erica A.; Kroetz, Deanna L.; Martin, Jeffrey; Hecht, Frederick; Pilcher, Christopher; Martin, Maureen; et al.
Abstract : Objective: Prior genomewide association studies have identified variation in major histocompatibility complex (MHC) class I alleles and C–C chemokine receptor type 5 gene ( CCR5Δ32 ) as genetic predictors of viral control, especially in 'elite' controllers, individuals who remain virally suppressed in the absence of therapy. Design: Cross-sectional genomewide association study. Methods: We analyzed custom whole exome sequencing and direct human leukocyte antigen (HLA) typing from 202 antiretroviral therapy (ART)-suppressed HIV+ noncontrollers in relation to four measures of the peripheral CD4 + T-cell reservoir: HIV intact DNA, total (t)DNA, unspliced (us)RNA, and RNA/DNA. Linear mixed models were adjusted for potential covariates including age, sex, nadir CD4 + T-cell count, pre-ART HIV RNA, timing of ART initiation, and duration of ART suppression. Results: Previously reported 'protective' host genetic mutations related to viral setpoint (e.g. among elite controllers) were found to predict smaller HIV reservoir size. The HLA 'protective' B∗57:01 was associated with significantly lower HIV usRNA ( q = 3.3 × 10 −3 ), and among the largest subgroup, European ancestry individuals, the CCR5Δ32 deletion was associated with smaller HIV tDNA ( P = 4.3 × 10 −3 ) and usRNA ( P = 8.7 × 10 −3 ). In addition, genomewide analysis identified several single nucleotide polymorphisms in MX1 (an interferon stimulated gene) that were significantly associated with HIV tDNA ( q = 0.02), and the direction of these associations paralleled MX1 gene eQTL expression. Conclusions: We observed a significant association between previously reported 'protective' MHC class I alleles and CCR5Δ32 with the HIV reservoir size in noncontrollers. We also found a novel association between MX1 and HIV total DNA (in addition to other interferon signaling relevant genes, PPP1CB, DDX3X ). These findings warrant further investigation in future validation studies.